Implications of hybridization, NUMTs, and overlooked diversity for DNA Barcoding of Eurasian ground squirrels. - Oleg A Ermakov; Evgeniy Simonov; Vadim L Surin; Sergey V Titov; Oleg V Brandler; Natalia V Ivanova; Alex V Borisenko (PLoS ONE)
The utility of DNA Barcoding for species identification and discovery has catalyzed a concerted effort to build the global reference library; however, many animal groups of economical or conservational importance remain poorly represented. This study aims to contribute DNA barcode records for all ground squirrel species (Xerinae, Sciuridae, Rodentia) inhabiting Eurasia and to test efficiency of this approach for species discrimination. Cytochrome c oxidase subunit 1 (COI) gene sequences were obtained for 97 individuals representing 16 ground squirrel species of which 12 were correctly identified. Taxonomic allocation of some specimens within four species was complicated by geographically restricted mtDNA introgression. Exclusion of individuals with introgressed mtDNA allowed reaching a 91.6% identification success rate. Significant COI divergence (3.5-4.4%) was observed within the most widespread ground squirrel species (Spermophilus erythrogenys, S. pygmaeus, S. suslicus, Urocitellus undulatus), suggesting the presence of cryptic species. A single putative NUMT (nuclear mitochondrial pseudogene) sequence was recovered during molecular analysis; mitochondrial COI from this sample was amplified following re-extraction of DNA. Our data show high discrimination ability of 100 bp COI fragments for Eurasian ground squirrels (84.3%) with no incorrect assessments, underscoring the potential utility of the existing reference librariy for the development of diagnostic 'mini-barcodes'.